The clinicopathological significance and relationship of Gli1, MDM2 and p53 expression in resectable pancreatic cancer. Issue 4 (2nd December 2013) - Sheng, Weiwei; Dong, Ming; Zhou, Jianping; Li, Xin; Liu, QingFeng; Dong, Qi; Li, Feng
<x xml:space="preserve">Abstract</x> Aims To study the expression of Gli1, MDM2 and p53 for clinical significance in pancreatic cancer (PC), and their functional relationship in regulating the biological behaviour of PC cells. Methods and results Immunohistochemistry showed that the expression of Gli1, MDM2 and p53 was much higher in 57 cases of PC than in paired normal pancreatic tissues, and was positively associated with tumour UICC stage and T stage (P < 0.05). Patients with expression of Gli1 only or coexpression of Gli1 and MDM2 had significantly worse overall survival than patients with negative expression (P < 0.05). RNA interference showed that p53 knockdown increased the protein level of Gli1 but decreased the level of MDM2, and enhanced cell invasion and migration in wild‐type p53 Capan‐2 cells; whereas Gli1 or MDM2 knockdown did not change p53 expression, but decreased the protein level of MDM2 or Gli1, respectively, and inhibited cell invasion and migration in mutant p53 PANC‐1 cells. Conclusions Overexpression of Gli1, MDM2 and mutant p53 contributes to the development and progression of PC, and plays an important role in predicting PC patients' prognosis. Moreover, we report a positive association between Gli1 and MDM2 in PC cells, but their relationship with p53 is dependent on wild‐type or mutant p53 status.